Pengaruh Faktor Fundamental, Economic Value Added dan Market Value Added Terhadap Return Saham pada Perusahaan Industri - Nadya Syafira Pudaya; Budi Kurniawan (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
This study uses quantitative research that aims to see whether there is an influence of fundamental factors, economic value added, market value added on stock returns. Measuring fundamental factors with 5 dimensions, namely: current ratio, return on assets, debt equity ratio, price book value, total asset turnover. The population in this study are all manufacturing companies listed on the Indonesia Stock Exchange (IDX) in the 2017-2019 period. The number of research samples obtained were 101 companies with purposive sampling method. Data analysis using multiple regression using. The results show that the current ratio, debt equity ratio, total asset turnover, and market value added have a positive effect on stock returns. Meanwhile, return on assets, price book value ,and economic value added have no effect on stock returns.